B2B Social Media Marketing Mix Optimization Model: A Case Study of a SME in Corporate Training Services - Devi Prasad Ghosh, (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2019)
The paper conceptualized a B2B Social Media Marketing Optimization Model by using Linear Programming mathematical technique. Social Media Marketing as part of digital marketing mix is seen as an effective one-to-one communication and an interactive media. But Social Media Marketing channels suffers from its poor reach compared to other digital media. As a practice, social media marketing is chosen as per ease of operation, lower cost and not on any quantitative measurements. The optimization model is first of its type since it uses media effectiveness (reach), media efficiency (Cost) and media quality (engagement) as the basis for building the optimization model. The concept presented takes into account complete cost of social media marketing that includes operations cost, production cost and design cost. The other model limits cost of Social Media Marketing to media cost only and usually account for production cost and design cost as a common marketing support cost, which in social media cases may consume a large portion of resources and cost. This also create problems to ascertain the cost in case of owned media or earned media where paid media cost is zero. The model also present a case that if Social Media Marketing Mix is chosen on basis of mathematical calculation, the outcome can be enhanced.